Finding God in Global Politics. Issue 2 (March 2015) - Maddox, Marion
The literature on religion and international politics has expanded in reaction to the events iconically known as '9/11', said to cast doubt on the 'secularisation thesis', which dominated the social sciences' approach to religion until the 1980s. The four books under review begin by assessing the secularisation premise, before amassing data to demonstrate the ways in which 'religion' (however conceived) influences or is suppressed by governments, inflames or mediates conflicts, shapes voter attitudes and political cultures, and so on. With one exception, the authors devote little attention to defining 'religion' or to delineating what differentiates it from other categories such as 'politics', 'culture', or 'ethnicity'. What 'religion' refers to, and how it relates to the 'secular', has been the subject of detailed, technical debate within the discipline of religious studies since 1962, but this literature is largely invisible in the four reviewed texts. The result is an enormous body of data which will overturn many enduring stereotypes; but whose usefulness is, in some cases, limited by the fact that the studies ultimately demonstrate that researchers tend to find what they go looking for.